How the social sciences talk about children and youth of African, Afroportuguese and black origins in Portugal: a critical state of the art (1990-2019) - Albuquerque, Adriana (Afroeuropean Studies Conference, 2019)
Despite Portugal’s long history of black and afrodescendant presence (Tinhorão, 1988), social sciences’ recognition of the numerically considerable mass of children, youth and young adult descendants of African parents living in Portugal as objects of study came late, only at the peak of the African labour migration flux from the mid-1980’s throughout the 1990’s. On the current year which marks the 45th anniversary of the former African colonies’ national liberation, the black and afrodescendant diaspora in Portugal is ever growing in number and diversity. It includes black Portuguese who have resided in the country for centuries (Ibid.), African immigrants who arrived during the post-decolonization migration waves – and their descendants, many of whom are adults born in Portugal – (Machado, 1994), as well as a recent but relevant influx of black Brazilians. Taking the ever-pressing existence of several generations of Portuguese black children and youth as backdrop, our paper focuses on how social-scientific literature has studied them for the past thirty years. Namely, it proposes to answer three questions: i) who the objects of research are; ii) who the producers (or subjects) of research are; and iii) how the research problems are framed. An exhaustive bibliographical survey was conducted on scientific documents – namely journal articles, working papers, books, book chapters, conference proceedings, technical reports and masters’/Ph.D. thesis’ – indexed in national databases of bibliographic references, such as PORBASE and RCAAP, which were then subject to content analysis. First, we systematize the main sociodemographic traits of black/afrodescendant children and youth, paying attention to the ways these have changed over the years in accordance to (or not) larger social developments and scientific debates. We then observe how much the objects and subjects of research overlap, i.e., how prevalent are black/afrodescendant researchers. Finally, we assess the nature of the theoretical and epistemological problem-building schemas adopted in the surveyed publications mainly by looking at the authors’ stance – implicit or explicit – concerning the character and centrality of race/racism in social processes involving black/afrodescendant children and youth. Taking this analysis as a starting point, we attempt to contribute to a reflexive considera- tion on the social, political and institutional conditions for social-scientific production concerning/by the black and afrodescendant diaspora in Portugal. Note: this paper was developed in the context of a doctoral research project financed by Fundação para a Ciência e a Tecnologia (FCT) titled “Trajetos das crianças descendentes de imigrantes no ensino básico: O poder dos contextos escolares na produção do sucesso [Trajectories of children of immigrants in primary school: The power of school contexts in the production of success]” – Grant reference SFRH/BD/135970/2018.